Computer-assisted virtual treatment planning combined with flapless surgery and immediate loading in the rehabilitation of partial edentulies - DE VICO, G. (CIC Edizioni Internationali, 2012)
It has been suggested that for success with immediate loaded dental implants it is necessary that, prior to their placement, bone quality and quantity as well as the biomechanical environment in which the implants are to function be evaluated. However, conventional techniques currently used for immediate implant placement lack sufficient precision and are usually accomplished by opening flap procedures. Nowadays computer-guided flapless surgery for implant placement using stereolithographic templates is gaining popularity among clinicians and patients. The advantages of this surgical protocol are its minimally invasive nature, accuracy of implant placement, predictability, less post-surgical disconfort and reduced time required for definitive rehabilitation. The introduction of digital planning programs has made it possible to place dental implants in preplanned positions and being immediately functionally loaded by using prefabricated prostheses. The surgical guide is used, infact, to develop a master model and fabricate the provisional bridge that will be secured to the implants immediately after their placement using the guided surgery template. In this way patients are able to achieve, in the same day of the surgery, a comfortable fixed rehabilitation needing only minor occlusal adjustments. Job S. et al during the three-month period, have demonstrated that the average reduction of crestal bone height around the implants placed with flapless surgery (0.06 mm) is not statistically significant, while the average reduction of crestal bone height around the implants placed using flap surgery (0.4 mm) is statistically significant, concluding that the use of stereolithographic appliances in accordance with flapless surgery makes immediate placement of the implants more predictable. However, the documentation of this technique in partial rehabilitations is limited. PURPOSE of this paper is to report the benefit of sophisticated pre-operative diagnostic implant planning and a flapless surgical approach with immediate loading in the rehabilitation of partial edentulies.